Terminal material for connector, manufacturing method thereof, and connector

The connector terminal material addresses the challenges of high friction, poor wear resistance, and increased contact resistance by employing a nickel-copper tin alloy-tin layer structure with controlled thickness and surface shape, resulting in improved performance under high temperature conditions.

JP7670224B1Active Publication Date: 2025-04-30MITSUBISHI MATERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024154278
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-01-24
Filing Date
2024-09-06
Publication Date
2025-04-30
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

Existing terminal materials for connectors face challenges in reducing friction coefficient, improving wear resistance, and maintaining low contact resistance, especially under high temperature environments.

Method used

A connector terminal material is developed with a specific structure comprising a nickel layer, a copper tin alloy layer, and a tin layer, where the copper tin alloy layer has a controlled surface shape and thickness, and the tin layer has a controlled thickness to optimize friction reduction and wear resistance.

Benefits of technology

The solution effectively reduces the friction coefficient, enhances wear resistance, and maintains low contact resistance, even under high temperature conditions, by controlling the surface shape and thickness of the copper tin alloy layer and the tin layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670224000001_ABST
    Figure 0007670224000001_ABST
Patent Text Reader

Abstract

The surface shape of the copper-tin alloy layer is controlled, the coefficient of friction is reduced, and the wear resistance and heat resistance are improved. [Solution] A coating is formed on the surface of a substrate made of copper or a copper alloy, and the coating has a nickel layer made of nickel or a nickel alloy formed on the surface of the substrate, a copper-tin alloy layer made of an alloy of copper and tin formed on the nickel layer, and a tin layer made of tin or a tin alloy formed on the copper-tin alloy layer, the average thickness of the nickel layer being 0.05 μm or more and 3.00 μm or less, and the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer being 700 mm -1 More than 2200mm -1 the average thickness of the tin layer is 0.05 μm or more and 2.00 μm or less, and the average thickness of the copper-tin alloy layer is 0.15 μm or more and 1.55 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a terminal material for a connector having a reduced coefficient of friction on the surface of the terminal material, a method for producing the same, and a connector. [Background technology]

[0002] Conventionally, there is known an on-board connector used for connecting electrical wiring in an automobile, etc. An on-board connector (on-board terminal) includes a terminal pair designed to be electrically connected by contacting a contact piece provided on a female terminal with a male terminal inserted into the female terminal at a predetermined contact pressure.

[0003] As such a connector (terminal), a terminal material with excellent wear resistance is known, which is formed by copper plating and tin plating on a copper or copper alloy plate and then performing a reflow process to form a copper-tin alloy layer and a tin layer on the copper or copper alloy plate.

[0004] As an example of a terminal material having such a copper-tin alloy layer and a tin layer, Patent Document 1 discloses a method for reducing the insertion force by controlling the roughness of the substrate and controlling the exposed state of the copper-tin alloy layer from the tin layer, but the substrate must be processed in advance to control its roughness.

[0005] In addition, in Patent Document 2, the insertion force is reduced by making the tin layer made of tin or a tin alloy on the copper-tin alloy layer very thin. However, since the tin layer is small, there is a problem that the contact resistance increases after heating.

[0006] In addition, in Patent Document 3, a part of the copper-tin alloy is replaced with nickel (Ni) to give the copper-tin alloy a steeply uneven shape, and a tin layer of 0.2 μm to 0.6 μm is left behind to reduce friction and prevent an increase in contact resistance during heating. However, because the copper-tin alloy layer is steep, it is easily scraped off during sliding, resulting in poor wear resistance. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2007-100220 A [Patent Document 2] JP 2011-012320 A [Patent Document 3] JP 2014-240520 A Summary of the Invention [Problem to be solved by the invention]

[0008] In the terminal materials described in these patent documents, in order to reduce the coefficient of friction, the tin layer on the surface is thinned and the proportion of the hard copper-tin alloy layer is increased. The soft tin layer on the surface is prone to adhesion during insertion and removal, which causes a problem of high insertion force. In order to prevent this adhesion, it is effective to expose the copper-tin alloy layer on the outermost surface, but this increases the contact resistance in high-temperature environments and lacks wear resistance against micro-sliding wear.

[0009] The present invention has been made in view of the above circumstances, and has an object to control the surface shape of a copper-tin alloy layer, reduce the coefficient of friction, and improve the wear resistance and heat resistance. [Means for solving the problem]

[0010] The terminal material for connectors of the present invention has a coating formed on the surface of a substrate made of copper or a copper alloy, and the coating has a nickel layer made of nickel or a nickel alloy formed on the surface of the substrate, a copper-tin alloy layer made of an alloy of copper and tin formed on the nickel layer, and a tin layer made of tin or a tin alloy formed on the copper-tin alloy layer, the nickel layer having an average thickness of 0.05 μm or more and 3.00 μm or less, and the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer is 700 mm. -1 More than 2200mm -1 the tin layer has an average thickness of 0.05 μm or more and 2.00 μm or less, and the copper-tin alloy layer has an average thickness of 0.15 μm or more and 1.55 μm or less.

[0011] The smaller the arithmetic mean curvature Spc of the peak, the more rounded the tip is, and the larger it is, the more pointed the tip is. -1 If the thickness is less than 2200 mm, the surface shape of the copper-tin alloy layer (the shape of the interface with the tin layer) becomes gentle and the contact area with the mating terminal increases, resulting in a high friction coefficient and a decrease in wear resistance. -1 If the thickness exceeds this value, the surface shape of the copper-tin alloy layer becomes sharper, so that the copper-tin alloy layer is more likely to be scraped off during sliding, resulting in an increase in the friction coefficient and a decrease in wear resistance.

[0012] In this case, if the average thickness of the tin layer is less than 0.05 μm, the contact resistance in a high temperature environment increases, whereas if it exceeds 2.00 μm, adhesive wear is likely to occur during sliding, and the friction coefficient increases. Furthermore, when the average thickness of the copper-tin alloy layer is less than 0.15 μm, the arithmetic mean curvature Spc of the peaks is small, resulting in a high friction coefficient and a low wear resistance.When the average thickness of the copper-tin alloy layer is more than 1.55 μm, the arithmetic mean curvature Spc of the peaks is large, resulting in a high friction coefficient and a low wear resistance. The nickel layer has the effect of preventing copper diffusion from the base material in a high-temperature environment, but if the average thickness is less than 0.05 μm, the effect of preventing copper diffusion from the base material is poor, and the rate at which the material turns into a copper-tin alloy increases, resulting in high contact resistance. If the average thickness of the nickel layer exceeds 3.00 μm, cracks may occur during bending.

[0013] In the terminal material for a connector of the present invention, it is preferable that the circularity of the copper-tin alloy particles on the surface of the copper-tin alloy layer is 0.5 or more.

[0014] The closer the circularity is to 1, the closer it is to a perfect circle, the more stable the contact point is, and the better the friction coefficient can be obtained. If the circularity is less than 0.5, the contact point function becomes uneven, the friction coefficient becomes slightly high, and the wear resistance decreases slightly.

[0015] In the terminal material for a connector of the present invention, a part of the copper-tin alloy layer is exposed on the surface of the tin layer, and an exposed area ratio of the copper-tin alloy layer on the surface of the tin layer is preferably 5% or more and 70% or less.

[0016] The copper-tin alloy layer, which is harder than the tin layer, is exposed on the surface, and the friction coefficient can be reduced by the lubricating effect of the soft tin layer. If the exposed area ratio of this copper-tin alloy layer is less than 5%, the effect of reducing the friction coefficient is small, and if the exposed area ratio exceeds 70%, the area occupied by the tin layer on the surface becomes small, which may increase the contact resistance in high-temperature environments.

[0017] The terminal material for a connector of the present invention preferably has a connection portion to be connected to a mating portion and a board fixing portion to be fixed to a board, and at least the connection portion is preferably coated with the coating. In this case, it is preferable that the substrate fixing portion has a tin surface layer made of tin or a tin alloy formed on the entire front, back and both side surfaces.

[0018] By forming the above-mentioned coating at least on the connection portion, the terminal has excellent insertability. In addition, for terminal materials for connectors that require fixing to a substrate, it is preferable to use a "post-plating method" in which a metal plate is plated after it is punched out, and it is preferable that the above-mentioned coating is formed at least on the connection portion that is connected to the other side, and that a tin surface layer made of tin or a tin alloy is formed over the entire surface of at least the portion that is fixed to the substrate. In the case of a pin-shaped terminal, a tin surface layer made of tin or a tin alloy is formed over the entire surface of the board fixing portion, resulting in a terminal with excellent solderability, and with the aforementioned coating formed at the connection portion with the mating side, the terminal also has excellent insertability.

[0019] The connector of the present invention has a first terminal and a second terminal that are connectable to each other, at least one of the first terminal and the second terminal is made of the connector terminal material, and a difference in arithmetic mean curvature Spc of peaks on the surface of the copper-tin alloy layer of the first terminal and the second terminal is 200 mm -1More than 1200mm -1 The following range is preferable.

[0020] The difference in the arithmetic mean curvature Spc of the peaks is 200 mm. -1 More than 1200mm -1 By setting the range below, the actual contact area is reduced, so that the sliding trace is reduced and the coefficient of friction can be further reduced.

[0021] Furthermore, when the difference in circularity of the copper-tin alloy particles on the surface of the copper-tin alloy layer between the one terminal and the other terminal is in the range of 0.4 or less, the coefficient of friction can be further reduced.

[0022] The method for producing a terminal material for a connector of the present invention includes a plating layer forming step of laminating a nickel plating layer made of nickel or a nickel alloy, a copper plating layer made of copper or a copper alloy, and a tin plating layer made of tin or a tin alloy in this order on a surface of a substrate made of copper or a copper alloy to form a substrate with a plating layer, and a reflow treatment step of carrying out a reflow treatment of heating the substrate with a plating layer, wherein in the plating layer forming step, the thickness of the nickel plating layer is 0.05 μm or more and 3.00 μm or less, the thickness of the copper plating layer is 0.10 μm or more and 0.70 μm or less, and the thickness of the tin plating layer is 0.20 μm or more and 2.90 μm or less. The reflow treatment process includes a first heating treatment in which the base material with the plating layer is passed through a first heating furnace set to a first furnace temperature of 150° C. or more and 270° C. or less in an air atmosphere for a time of 3 seconds or more and 30 seconds or less to heat the base material with the plating layer to a temperature lower than the melting point of tin, a second heating treatment in which, after the first heating treatment, the base material with the plating layer is passed through a second heating furnace set to a second furnace temperature of 232° C. or more and 350° C. or less, which is higher than the first furnace temperature, for a time of 3 seconds or more and 35 seconds or less to heat the base material with the plating layer, and a cooling treatment in which the base material with the plating layer is quenched immediately after the tin plating layer is melted by the second heating treatment.

[0023] By performing the reflow treatment process as a two-stage heating process under a predetermined temperature condition and then cooling, the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer described above can be controlled within a predetermined range. Although the plating layer changes during the reflow treatment process, the substrate is called a substrate with a plating layer until the reflow treatment process is completed.

[0024] If the heating in the reflow process is insufficient, the average thickness of the copper-tin alloy layer will be less than 0.15 μm, and if the heating in the reflow process is excessive, the average thickness of the copper-tin alloy layer will exceed 1.55 μm. In the second heat treatment of this reflow process, the outermost tin plating layer melts and becomes glossy, and then the cooling process is immediately started. Therefore, in this second heat treatment, the substrate with the plating layer is always in an elevated temperature state and is not maintained at the peak temperature at which the tin melts.

[0025] Here, the shape of the copper-tin alloy layer is affected by the thickness of the tin plating layer and the copper plating layer as well as the reflow treatment conditions. The influence of the thickness of the tin plating layer and the copper plating layer will be explained below. When the thickness of the copper plating layer is 0.10 μm or more but the thickness of the tin plating layer is less than 0.20 μm, the copper plating layer remains, Spc becomes small, the friction coefficient becomes high, and the wear resistance decreases. In addition, the contact resistance increases because the tin layer is thin. When the thickness of the copper plating layer is less than 0.10 μm, part of the copper-tin alloy is replaced by nickel, so the shape of the copper-tin alloy layer becomes steep, Spc becomes large, the friction coefficient becomes high, and the wear resistance decreases.

[0026] In the cooling treatment, the cooling time until the temperature of the base material with a plating layer reaches 50° C. is preferably set to 4 seconds or more and 60 seconds or less. Effect of the Invention

[0027] According to the present invention, the surface of the copper-tin alloy layer is controlled to have a predetermined shape, thereby making it possible to reduce the coefficient of friction and improve the wear resistance and heat resistance. [Brief description of the drawings]

[0028] [Figure 1] 1 is a plan view of a terminal material for a connector according to an embodiment of the present invention; [Diagram 2] 2 is a schematic cross-sectional view of the connector terminal material of FIG. 1. [Diagram 3] 2 is a flowchart showing a method for manufacturing the connector terminal material of FIG. 1. [Figure 4] 3 is a schematic cross-sectional view showing a substrate with a plating layer of the connector terminal material of FIG. 2 before a reflow treatment step. FIG. [Diagram 5] 1 is a backscattered electron (BSE) image of a cross section of sample 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.

[0030] [Configuration of connector terminal materials] As shown in FIG. 1, the terminal material 1 for a connector of this embodiment is a chained-terminal body formed by connecting a plurality of terminal portions 10 in the shape of a pin terminal, and is formed by punching out a long plate material by press working. Specifically, a plurality of terminal portions 10 are provided in parallel between a pair of elongated connecting members 11, 12 along the direction connecting the two connecting members 11, 12. Each terminal portion 10 has a pin-shaped connecting portion 13, a wide shoulder portion 14, and a board fixing portion 15 formed continuously from the tip, and both ends (the tip of the connecting portion 13 and the base end of the board fixing portion 15) are connected to the connecting members 11, 12, respectively. This terminal portion 10 is used by fixing it to a board or the like in an electrically connected state by pressing or soldering the board fixing portion 15 into a through hole or the like of the board, and the electrical connection is made by inserting the connecting portion 13 into another female terminal. The shape of the terminal is merely an example and is not limited to that shown in FIG. 1, and may be any shape having a connection portion for electrical connection with a mating terminal.

[0031] As shown in the cross section of FIG. 2, this connector terminal material 1 has a coating 22 formed on a substrate 21 made of copper or a copper alloy, and the coating 22 is made up of a nickel layer 23 made of nickel or a nickel alloy, a copper-tin alloy layer 24 made of an alloy of copper and tin, and a tin layer 25 made of tin or a tin alloy, which are formed in this order. FIG. 2 shows a cross section in the thickness direction, and the coating 22 is formed on the entire surfaces of both the front and back sides of the substrate 21.

[0032] The composition of the base material 21 is not particularly limited as long as it is made of copper or a copper alloy, and it is formed, for example, from a plate material made of copper or a copper alloy such as oxygen-free copper (C10200), Cu-Mg copper alloy (C18665), brass, phosphor bronze, etc.

[0033] The nickel layer 23 has a function of suppressing the diffusion of copper from the base material 21 to the copper-tin alloy layer 24 and the tin layer 25 formed thereon. The average thickness (film thickness) of the nickel layer 23 is 0.05 μm or more and 3.00 μm or less. If the average thickness of the nickel layer 23 is less than 0.05 μm, the effect of preventing the diffusion of copper from the base material 21 in a high-temperature environment is poor, and the rate at which the nickel layer becomes a copper-tin alloy increases, resulting in high contact resistance. On the other hand, if the average thickness of the nickel layer 23 exceeds 3.00 μm, there is a possibility that cracks will occur during bending. The composition of the nickel layer 23 is not particularly limited as long as it is made of nickel or a nickel alloy. The average thickness of the nickel layer 23 is preferably 0.10 μm or more and 2.00 μm or less.

[0034] The copper-tin alloy layer 24 is a layer obtained by successively forming a copper plating layer and a tin plating layer on the nickel layer 23 and performing a reflow treatment. The surface of the copper-tin alloy layer 24, i.e., the interface with the tin layer 25 thereon, is formed in an uneven shape, and a part of it is exposed on the surface of the tin layer 25. The average thickness of the copper-tin alloy layer 24 is 0.15 μm or more and 1.55 μm or less. The average thickness of the copper-tin alloy layer 24 and the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 are affected by the reflow treatment conditions described later and the thicknesses of the tin plating layer 33 and the copper plating layer 32 during production. Regarding the influence of the reflow treatment conditions, first, when the average thickness of the copper-tin alloy layer 24 is less than 0.15 μm due to insufficient heating in the reflow treatment, the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 described later is small, the exposed area ratio on the surface of the tin layer 25 is reduced, and the friction coefficient is increased. In addition, the average thickness of the hard copper-tin alloy layer 24 is thin, so the wear resistance is reduced. On the other hand, when the average thickness of the copper-tin alloy layer 24 exceeds 1.55 μm due to excessive heating in the reflow treatment, the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 is large, the friction coefficient is high, and the wear resistance is reduced. The influence of the thickness of the tin plating layer 33 and the copper plating layer 32 during manufacturing is as follows: first, the thickness of the copper plating layer is 0.10 μm or more, but if the thickness of the tin plating layer is less than 0.20 μm, the copper plating layer remains, Spc becomes small, the friction coefficient becomes high, and the wear resistance decreases. In addition, the contact resistance increases because the tin layer is thin. On the other hand, if the thickness of the copper plating layer is less than 0.10 μm, part of the copper-tin alloy is replaced by nickel, so the shape of the copper-tin alloy layer becomes steep, Spc becomes large, the friction coefficient becomes high, and the wear resistance decreases.

[0035] In addition, the exposed area ratio of the copper-tin alloy layer 24 on the surface of the tin layer 25 is preferably 5% or more and 70% or less. The copper-tin alloy layer 24, which is harder than the tin layer 25, is exposed on the surface, and the friction coefficient can be reduced in combination with the lubricating effect of the soft tin layer 25. If the exposed area ratio of the copper-tin alloy layer 24 is less than 5%, the effect of reducing the friction coefficient is poor, and the surface area of ​​the tin layer 25 increases accordingly, which may cause adhesive wear to occur more easily and increase the friction coefficient. In addition, the wear resistance may also decrease. If the exposed area ratio exceeds 70%, the area occupied by the tin layer 25 on the surface is reduced, which may increase the contact resistance in a high-temperature environment. It is more preferable that the exposed area ratio of the copper-tin alloy layer 24 is 10% or more and 50% or less.

[0036] In addition, the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 measured after removing the tin layer 25 was 700 mm -1 More than 2200mm -1 The arithmetic mean curvature Spc of the peak is a parameter measured in accordance with ISO 25178, and the smaller the value, the more rounded the tip is, and the larger the value, the more pointed the tip is. -1 If the thickness is less than 100 nm, the surface shape of the copper-tin alloy layer 24 (the shape of the interface with the tin layer 25) becomes gentle. Also, the exposed area ratio decreases, and the area occupied by the tin layer 25 on the surface of the coating 22 tends to increase accordingly. This results in a high friction coefficient and a low wear resistance.

[0037] On the other hand, the arithmetic mean curvature Spc of the peak is 2200 mm -1 If the surface shape of the copper-tin alloy layer 24 exceeds 900 mm, the copper-tin alloy layer 24 becomes sharper, so that the copper-tin alloy layer 24 is more likely to be scraped off during sliding, and the friction coefficient increases. In addition, the wear resistance decreases. The arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 is 900 mm. -1 More than 1900mm -1 The following is preferred:

[0038] Furthermore, the degree of circularity of the copper-tin alloy particles on the surface of the copper-tin alloy layer 24 (at the interface with the tin layer 25) is preferably 0.5 or more. This degree of circularity is calculated by the following formula: 4π × (particle area) ÷ (perimeter) 2 The closer the circularity of the copper-tin alloy particles is to 1, the closer they are to a perfect circle, and because they are arranged in a nearly circular state when viewed from the surface, they provide a stable contact point and a low coefficient of friction.

[0039] If the circularity of the copper-tin alloy particles is less than 0.5, the copper-tin alloy layer 24 exposed on the surface of the tin layer 25 during sliding as a connector may have an uneven contact point with the mating terminal that slides, resulting in a high friction coefficient. In addition, the wear resistance is somewhat reduced. The circularity of the copper-tin alloy particles is more preferably 0.55 or more. The higher the circularity of the copper-tin alloy particles, the lower the friction coefficient and the better the result, but it is actually difficult to control the shape of the copper-tin alloy layer 24 to a circularity of more than 0.85.

[0040] The tin layer 25 is a layer made of tin or a tin alloy, and is formed to have an average thickness of 0.05 μm or more and 2.00 μm or less. If the average thickness of this tin layer is less than 0.05 μm, the contact resistance in a high temperature environment increases, and if it exceeds 2.00 μm, adhesive wear is likely to occur and the friction coefficient increases. In addition, the exposed area ratio of the copper-tin alloy layer 24 also decreases. The average thickness of this tin layer 25 is preferably 0.05 μm or more and 1.00 μm or less, and more preferably 0.10 μm or more and 0.50 μm or less.

[0041] [Method of manufacturing connector terminal material] Next, a method for manufacturing this connector terminal material 1 will be described. 3, the method of manufacturing this terminal material for connector 1 includes a punching step of punching a long and narrow plate material with a press to form a chain of terminals that will become base material 21, a pretreatment step of cleaning the surface of base material 21 after punching, a plating layer forming step of forming nickel plating layer 31, copper plating layer 32, and tin plating layer 33 in this order on the surface of base material 21, and a reflow treatment step of heating and reflowing base material 35 with plating layers formed thereon, on which the three plating layers 31 to 33 have been formed. The steps will be described below in order.

[0042] (Punching process) A long and thin plate material wound in a coil shape is punched out by a press while being unwound, to form a chain of terminals that serves as a base material 21 as shown in FIG.

[0043] (Pretreatment process) After punching, the base material 21 is subjected to pretreatment such as degreasing and pickling to clean the surface.

[0044] (Plating layer formation process) - Nickel plating layer - The pretreated surface of the substrate 21 is subjected to a nickel plating process to form a nickel plating layer 31 made of nickel or a nickel alloy. A typical nickel plating bath may be used as the plating bath, and for example, a sulfamate bath containing nickel sulfamate, nickel chloride, or boric acid as the main component may be used. The temperature of the plating bath is 40° C. or higher and 60° C. or lower, and the current density is 1 A / dm 2 More than 10A / dm 2 The thickness of this nickel plating layer 31 is set to be 0.05 μm or more and 3.00 μm or less.

[0045] -Copper plating layer- A copper plating process is carried out on the nickel plating layer 31 to form a copper plating layer 32 made of copper or a copper alloy. A general copper plating bath may be used for the copper plating, and for example, a copper sulfate bath containing copper sulfate and sulfuric acid as main components may be used. The temperature of the plating bath is 20° C. or higher and 60° C. or lower, and the current density is 1 A / dm 2 More than 10A / dm 2 The following is stated.

[0046] The thickness of the copper plating layer 32 is 0.10 μm or more and 0.70 μm or less. If the thickness of the copper plating layer is 0.10 μm or more but the thickness of the tin plating layer is less than 0.20 μm, the copper plating layer remains after the reflow treatment process, Spc becomes small, the friction coefficient becomes high, and the wear resistance decreases. If the thickness of the copper plating layer 32 exceeds 0.70 μm, the exposed area ratio of the copper-tin alloy layer 24 exposed from the surface of the tin layer 25 after the reflow treatment process increases, and the contact resistance may increase. On the other hand, if the thickness of the copper plating layer 32 is less than 0.10 μm, a part of the copper-tin alloy is replaced by nickel, so that the shape of the copper-tin alloy layer becomes steep, Spc becomes large, the friction coefficient becomes high, and the wear resistance may decrease. There is also a possibility that the exposed area ratio of the copper-tin alloy layer 24 becomes small. The thickness of the copper plating layer 32 is preferably 0.20 μm or more and 0.50 μm or less.

[0047] -Tin plating layer- A tin plating process is carried out on the copper plating layer 32 to form a tin plating layer 33 made of tin or a tin alloy. A typical tin plating bath may be used as the plating bath for forming the tin plating layer 33, and for example, a methanesulfonic acid bath containing methanesulfonic acid and tin methanesulfonate as the main components may be used. The temperature of the plating bath is 20° C. or higher and 40° C. or lower, and the current density is 1 A / dm 2 More than 20A / dm 2 The following is stated.

[0048] The thickness of this tin plating layer 33 is set to 0.20 μm or more and 2.90 μm or less. If the thickness of the tin plating layer 33 is less than 0.20 μm, the average thickness of the tin layer 25 after the reflow treatment process will be thin, which may increase the contact resistance in a high-temperature environment. If the thickness of the tin plating layer 33 exceeds 2.90 μm, the tin layer 25 after the reflow treatment process will be thick, the exposed area ratio of the copper-tin alloy layer 24 will decrease, and adhesive wear will be more likely to occur, which may increase the friction coefficient. The thickness of this tin plating layer 33 is more preferably 0.20 μm or more and 1.30 μm or less, and even more preferably 0.40 μm or more and 1.00 μm or less.

[0049] In this manner, the nickel plating layer 31, the copper plating layer 32, and the tin plating layer 33 are successively formed on the surface of the base material 21, thereby obtaining a base material 35 with plating layers, in which the three plating layers 31-33 are laminated, as shown in Fig. 4. In this case, the base material 21 before plating is in a state where it has been punched into a chain terminal shape by a press, and the base material 21 is immersed in a plating bath to form the plating layers 31-33, so that the three plating layers 31-33 are formed not only on the front and back surfaces of the base material 21 but also on both side surfaces (the cut end surfaces during punching). However, the present invention can also be used in a "partial plating" process in which a portion of the base material is immersed in a plating bath.

[0050] (Reflow processing process) The plated layer-attached substrate 35 on which the plated layers 31 to 33 have been formed as described above is subjected to a reflow treatment. In this reflow treatment step, in the case of a long and narrow plate material (strip material) wound on a roll, the plate material is run in the length direction and passed through a reflow furnace while the above-mentioned pretreatment and plating treatment are continuously performed, but in the case of the plated layer-attached substrate 35 of this embodiment, it is a punched material that has been punched out in advance by a press into a chain of terminals of a predetermined length as shown in Fig. 1, and after the above-mentioned pretreatment and plating treatment are performed on this punched material, the plated layer-attached substrate 35 is supplied to a relatively small reflow furnace for reflow treatment.

[0051] Specifically, the method includes a first heating process in which the plated layer-formed substrate 35 is passed through a first heating furnace set to a first furnace temperature of 150° C. or more and 270° C. or less in an air atmosphere for a time period of 3 seconds or more and 30 seconds or less to heat the substrate 35 to a temperature below the melting point of tin; a second heating process in which the plated layer-formed substrate 35 is passed through a second heating furnace set to a second furnace temperature of 232° C. or more and 350° C. or less, which is higher than the first furnace temperature, for a time period of 3 seconds or more and 35 seconds or less; and a cooling process in which the plated layer-formed substrate 35 is quenched immediately after the tin plating layer is melted by the second heating process.

[0052] In this reflow treatment process, a two-stage heating process is performed in which the tin plating layer 33 is heated to a temperature just before it melts, and then the tin plating layer 33 is further reflowed and melted, so that the copper-tin alloy particles and tin particles formed by the copper plating layer 32 and the tin plating layer 33 can be gradually grown and controlled to have a rounded shape. This makes it possible to control the arithmetic mean curvature Spc and circularity of the peaks on the surface of the copper-tin alloy layer 24 described above within a predetermined range. The atmosphere for the first and second heat treatments in this reflow process may be air, and water vapor may be additionally introduced.

[0053] In this case, in the first heat treatment, the temperature inside the furnace may be as high as 270°C, but the plated layer-attached substrate 35 does not rise to the melting temperature of tin, and therefore the tin plating layer 33 does not melt at this stage. This first heat treatment is a preliminary step for quickly melting the tin plating layer 33 in the second heat treatment. In this first heating process, if the temperature in the first furnace is less than 150°C or the time is less than 3 seconds, the heating is insufficient, the formation of the copper-tin alloy in the second heating process is insufficient, and it becomes difficult to form the copper-tin alloy layer 24 with the desired average thickness. Furthermore, the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer described above is small, and the circularity is small, making it difficult to reliably control it within a predetermined range. On the other hand, if the temperature in the first furnace exceeds 270°C or the temperature of the plated layer-attached substrate 35 becomes equal to or higher than the melting point of tin and the tin plating layer 33 melts in the first heating process, the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 becomes large, and the wear resistance decreases. In addition, the tin layer 25 becomes thin, and the contact resistance increases. If the time exceeds 30 seconds, overheating occurs, the tin layer 25 becomes thin, and the contact resistance increases.

[0054] In the second heating process, if the temperature in the second furnace is less than 232°C or the time is less than 3 seconds, the formation of the copper-tin alloy becomes insufficient, making it difficult to form the copper-tin alloy layer 24 with the desired average thickness, and Spc becomes small, so that the friction coefficient increases and the wear resistance decreases. On the other hand, if the temperature in the second furnace exceeds 350°C, overheating occurs, and the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 increases, so that the friction coefficient increases and the wear resistance decreases. In addition, the tin layer 25 becomes thin and the contact resistance increases. Similarly, if the temperature in the first furnace and the temperature in the second furnace both exceed a predetermined temperature, overheating occurs, and the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 increases, so that the friction coefficient increases and the wear resistance decreases. In addition, the tin layer 25 becomes thin and the contact resistance increases. If the time of the second heating process exceeds 35 seconds, the tin layer 25 becomes thin and the contact resistance increases. However, if the tin plating layer 33 is thick or the copper plating layer 32 is thin, the tin layer 25 will become thick even if the heating temperature is high or the heating time is long. This second heat treatment melts the tin plating layer of the plated layer-formed substrate 35. The melting of the tin plating layer can be confirmed because the surface changes from white to a glossy silver color when the tin of the plated layer-formed substrate 35 melts. In this second heat treatment, the outermost tin plating layer melts and becomes glossy, and then the cooling process is immediately started. Therefore, in this second heat treatment, the plated layer-attached substrate 35 is always in an elevated temperature state and is not maintained at the peak temperature at which the tin melts.

[0055] In this reflow process, the relationship between the furnace temperature and the time it takes to pass through the furnace is such that the higher the furnace temperature, the shorter the time. For example, in the first heating process, if the furnace temperature is closer to 150°C, the time is longer at about 30 seconds, and if the furnace temperature is closer to 270°C, the time is shorter at about 3 seconds. The same is true for the second heating process, where if the furnace temperature is closer to 232°C, the time is longer at about 35 seconds, and if it is closer to 350°C, the time is shorter at about 3 seconds. In this case, the relationship between the furnace temperature and the time may be subdivided within a predetermined temperature range, for example, in the first heating process, the time is more than 19 seconds and not more than 30 seconds when the furnace temperature is 150°C or more and less than 200°C, more than 8 seconds and not more than 19 seconds when the furnace temperature is 200°C or more and less than 250°C, and 3 seconds or more and not more than 8 seconds when the furnace temperature is 250°C or more and less than 270°C, and in the second heating process, the time is more than 23 seconds and not more than 35 seconds when the furnace temperature is 232°C or more and less than 280°C, more than 11 seconds and not more than 23 seconds when the furnace temperature is 280°C or more and less than 320°C, and 3 seconds or more and not more than 11 seconds when the furnace temperature is 320°C or more and less than 350°C. This method of subdivision may be set in consideration of ease of management, etc.

[0056] In addition, in the cooling process, the cooling time until the temperature of the plated layer-attached substrate 35 reaches 50° C. is preferably set to 4 seconds or more and 60 seconds or less. Under atmospheric cooling conditions, it is physically difficult to cool the plated layer-attached substrate 35 to 50° C. in a cooling time of less than 4 seconds. If the plated layer-attached substrate 35 is cooled to 50° C. for a cooling time of more than 60 seconds, the formation of a copper-tin alloy is not sufficiently suppressed, and the alloy shape is no longer circular, and the circularity may be reduced. This cooling treatment is started immediately after the tin plating layer of the plated layer-formed substrate 35 is melted in the second heating treatment, for example, within 2 seconds, preferably within 1 second after melting. Strictly speaking, cooling of the plated layer-formed substrate 35 starts near the exit of the second heating furnace. The plated layer-formed substrate 35 may be cooled by blowing cold air or water on the plated layer-formed substrate 35 that has come out of the second heating furnace, passing the plated layer-formed substrate 35 through a water tank, or the like.

[0057] By carrying out the reflow treatment in this manner, the nickel layer 23, the copper-tin alloy layer 24, and the tin layer 25 are formed in this order as the coating 22 on the substrate 21. As described above, since the plating layers 31-33 are formed not only on the front and back surfaces of the substrate 21 but also on both side surfaces, the coating 22 consisting of the nickel layer 23, the copper-tin alloy layer 24, and the tin layer 25 is formed on both side surfaces as well as on the front and back surfaces, and the entire surface of the substrate 21 is covered with the coating 22. During the reflow treatment, the copper of the copper plating layer 32 and the tin of the tin plating layer 33 react to form the copper-tin alloy layer 24 and the tin layer 25. However, some of the copper of the copper plating layer 32 may remain unreacted, and a thin copper layer may exist between the nickel layer 23 and the copper-tin alloy layer 24.

[0058] In the case of a pin-shaped terminal using the terminal material 1 of this embodiment, as shown in Fig. 1, the connection portion 13 to be connected to the mating terminal is formed in a long and thin pin shape, so that not only the front and back surfaces of the terminal material 1 but also the side surfaces may come into contact with the mating terminal. In addition, since the coating 22 is formed on the entire surface, corrosion is unlikely to occur.

[0059] Furthermore, as a result of the inventors' thorough research, they discovered that by optimizing the shapes of both copper-tin alloy layers in the combination of terminals, the developed product can achieve even lower friction when the terminals slide. In other words, in a pair of terminals that are in a mutually mated state, the difference in the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer 24 is set to 200 mm. -1 More than 1200mm -1 An even lower friction can be obtained by setting the difference in circularity of the copper-tin alloy particles on the surface of the copper-tin alloy layer 24 to the range of 0.4 or less.

[0060] The difference between the Spc of the female terminal material and the Spc of the male terminal material is 200 mm -1 More than 1200mm -1 In the following cases, the unevenness of the copper-tin alloy layer 24 is appropriately different, so that when sliding, the copper-tin alloy layer 24 has multiple contact points, the pressure at each contact point is small, and the force is dispersed, so that the friction coefficient is low and the amount of wear is reduced.

[0061] In the case of such a combination of terminals, the above-mentioned coating 22 may be formed on at least one of the terminals. For the other terminal, for example, the arithmetic mean curvature Spc or the circularity of the peaks on the surface of the copper-tin alloy layer 24 may be within the numerical range described in the embodiment (Spc is 700 mm -1 More than 2200mm -1 Hereinafter, the circularity may be outside the range of 0.5 or more.

[0062] In addition, the detailed configuration is not limited to that of the embodiment, and various modifications can be made without departing from the spirit of the present invention. In the terminal material for connector 1 of the embodiment, this coating 22 is formed on the entire surface of the substrate 21, but it is sufficient that it is formed at least on the connection portion 13. Even in this connection portion 13, the coating 22 need not be formed on the entire surfaces of both the front and back sides and both sides, but only needs to be formed in the portion that comes into contact with the mating member. Furthermore, the substrate fixing portion 15 may be configured such that, instead of this coating 22, a tin surface layer made of tin or a tin alloy is formed on the entire surface (front and back sides and both sides). When the coating 22 is formed on the substrate fixing portion 15, the tin surface layer becomes the tin layer 25. EXAMPLES

[0063] The substrate was made of a 0.40 mm thick sheet of alloy C18665 (CDA, Copper Development Association) alloy, which was punched into the shape of the chain of terminals shown in the figure. After that, electrolytic degreasing and pickling were performed as pretreatment, and the surface was nickel-plated, copper-plated, and tin-plated in that order. Pickling was also performed between the nickel plating and the copper plating. The conditions for electrolytic degreasing, pickling, and plating are shown in Table 1 in the order of the steps, and the same conditions were used for the following examples and comparative examples. In the table, RT stands for room temperature.

[0064] [Table 1]

[0065] The substrates with plated layers having various thicknesses were then subjected to a reflow treatment. The thickness of each plated layer and the reflow conditions are shown in Table 2. The cooling time is the time required for the temperature of the substrate with plated layers to reach 50°C. When measuring the thickness of each plating layer before and after the reflow treatment, the measurement was performed at part A in Fig. 1. Part A is the central part of the connection part 13 of the terminal. Regarding the thickness of the copper layer and the copper-tin alloy layer in part A where the three plating layers were formed, the sample was cut, and the cut surface was embedded in resin so as to be the observation area, and then polished and processed with a CP (cross-section polisher). The cross-sectional backscattered electron image was observed using a Reguls8230 scanning electron microscope manufactured by Hitachi High-Tech Corporation, and the thickness was measured at 10 random locations, and the average was calculated. The thicknesses of the tin layer and the nickel layer in part A were measured using a fluorescent X-ray film thickness meter (FT150) manufactured by Hitachi High-Tech Science Corporation.

[0066] [Table 2]

[0067] For the terminal material after reflow treatment, the average thickness of each layer of the coating, the arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer, the circularity of the copper-tin alloy particles on the surface of the copper-tin alloy layer, and the exposed area ratio of the copper-tin alloy layer on the surface of the tin layer were measured, and the wear resistance (wear amount), friction coefficient, and contact resistance were evaluated.

[0068] (average thickness of each layer) When measuring the average thickness of each layer, the measurement was performed at part A in Figure 1. Part A is the center part of the connection part of the terminal. The thicknesses of the tin layer and the nickel layer were measured with a fluorescent X-ray film thickness meter (FT150) manufactured by Hitachi High-Tech Science Corporation. Regarding the average thickness of the tin layer before and after the reflow treatment, first, the thickness of the tin-containing layer (layer containing tin: the entire tin layer and the copper-tin alloy layer) of the sample after the reflow treatment was measured, and then the tin layer was removed by immersing the sample for several minutes in an etching solution for removing a tin plating film, which contains components that do not etch tin but corrode the copper-tin alloy, such as L80 manufactured by Leybold Co., Ltd., and the average thickness of the tin layer was defined as the thickness of the tin-containing layer after etching subtracted from the thickness of the tin-containing layer before etching.

[0069] The average thickness of the copper-tin alloy layer was measured by cutting the sample, embedding the cut surface in resin so that it would be the observation area, polishing and CP (cross-section polisher) processing, and observing the cross-sectional backscattered electron image using a scanning electron microscope Reguls8230 manufactured by Hitachi High-Tech Corporation. The thickness was measured at 10 arbitrary points at the distance a between the peaks of the nickel layer and the copper-tin alloy layer and the distance b between the nickel layer and the copper-tin alloy layer in Figure 2, which shows a schematic diagram of the cross section, and the height of the copper-tin alloy layer was calculated as (a+b) / 2, and the average was calculated.

[0070] (Arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer) The arithmetic mean curvature Spc of the apex of the protrusion in part A in Figure 1 was measured by immersing the sample in an etching solution for removing the tin plating film to remove the tin layer and exposing the copper-tin alloy layer underneath, and then measuring Spc over a 20 μm square area using a laser microscope (VK-X200) manufactured by Keyence Corporation at a magnification of 150 (measurement field of view 96 μm × 72 μm), and filtering the data obtained by setting the cutoff wavelength of the S filter to 1 μm and the cutoff wavelength of the L filter to 0.1 mm. The average value of Spc measured at a total of five points was obtained.

[0071] (Circularity of copper-tin alloy particles on the surface of the copper-tin alloy layer) The specimen was immersed in an etching solution for removing tin plating to remove the tin layer and expose the copper-tin alloy layer underneath. The measurement area was designated as area A, and the specimen was scanned at a magnification of 4000 times to a resolution of 0.0008 mm using a SEM (Scanning Electron Microscope) (JCM-7000 manufactured by JEOL Ltd.). 2 The secondary electron image of the field of view was observed. The circularity, which indicates the degree of circularity, is calculated as 4π × (alloy area) ÷ (perimeter) 2 The circularity of the copper-tin alloy particles was calculated by extracting the edge of the copper-tin alloy particles from the secondary electron images obtained above using the well-known image processing software Image J (ver. 1.54f). The circularity of at least 10 copper-tin alloy particles was obtained per secondary electron image and averaged to obtain the circularity.

[0072] (Exposed area ratio of copper-tin alloy layer on the surface of tin layer) The measurement area was designated as area A, and a scanning electron microscope (SEM) (JSM-7001F manufactured by JEOL Ltd.) was used to measure the area at a magnification of 2000 times and a resolution of 0.0028 mm. 2 The backscattered electron image of the field of view was observed. The backscattered electron image obtained above was binarized using the well-known image processing software Image J (ver. 1.54f) so that the Cu-Sn alloy layer exposed on the surface was black and the Sn layer was white, and the exposed area rate was calculated by determining the area of ​​the Cu-Sn alloy layer. The binarization was performed with an altitude range of 255 set to 112.

[0073] (Wear amount) Each sample was cut into a test piece 60 mm long parallel to the rolling direction and used as a substitute for a male terminal (male terminal test piece). The female terminal test piece was made by cutting sample 31 in Table 3, which was not processed into a terminal shape, into a size of 60 mm x 10 mm and embossing the center of the test piece with a curvature radius of 2.5 mm. The test was performed using a friction and wear tester (UMT-Tribolab) made by Bruker AXS Co., Ltd. The convex surface of the female terminal test piece was brought into contact with part A in Figure 1, which is the sliding part of the horizontally placed male terminal test piece, and the male terminal test piece was slid back and forth over a distance of 1 mm 500 times while applying a load of 1 N to the male terminal test piece. For the measurement, a white light interference microscope (NexView8300 made by Ametech Co., Ltd.) was used to observe the sliding marks on the male terminal sample at 20 times magnification in the depth direction in a direction perpendicular to the sliding. The amount of wear is calculated by taking the cross-sectional wear area of ​​the deepest wear position and calculating the area of ​​wear when it is 300μm 2 A is less than 300μm 2 More than 1200μm 2 The following are B, 1200μm 2 Those exceeding this were rated C.

[0074] (Coefficient of friction) Each sample was cut into a test piece with a length of 60 mm parallel to the rolling direction and used as a substitute for a male terminal (male terminal test piece). The female terminal sample was made common to all samples, and was made by cutting sample 31 in Table 3, which was not processed into a terminal shape, into a size of 60 mm x 10 mm and embossing the center of the test piece with a curvature radius of 2.5 mm. The friction coefficient of this test piece sample was measured. For the measurement, a friction and wear tester (UMT-Tribolab) made by Bruker AXS Co., Ltd. was used, and the convex surface of the female terminal test piece was brought into contact with a position 5 mm below part A in the terminal diagram 1 showing the male terminal test piece placed horizontally, so that part A was the center of the sliding part, and the male terminal test piece was slid for a distance of 10 mm to a position 5 mm above part A while applying a load of 5 N. Friction coefficient data was obtained every 0.013 mm of sliding distance, and the average value of the friction coefficients obtained at distances of 0.1 mm to 10 mm was taken as the friction coefficient value.

[0075] (contact resistance) Test pieces were prepared in the same way as for the coefficient of friction, except that the embossing radius was 1.5 mm. After heating these at 150°C for 250 hours, the contact resistance (mΩ) of each was measured. For the measurement, a friction and wear tester (UMT-Tribolab) made by Bruker AXS was used, and the convex surface of the female test piece was brought into contact with the horizontally placed male terminal test piece, and the contact resistance was measured using the four-terminal method when a load of 5 N was applied to the male terminal test piece.

[0076] For those in which cracks occurred during indentation, evaluations of the friction coefficient, wear amount, and contact resistance were not performed.

[0077] The results of these measurements are shown in Table 3.

[0078] [Table 3]

[0079] All of the samples 1 to 30 had low friction coefficients, wear amounts, and contact resistances, and were good. These samples had nickel layers with average thicknesses of 0.05 μm to 3.00 μm, tin layers with average thicknesses of 0.05 μm to 2.00 μm, and copper-tin alloy layers with average thicknesses of 0.15 μm to 1.55 μm. The arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer was 700 mm. -1 More than 2200mm -1 It is within the following range. Of these, samples 4 and 19 had slightly more wear than the others because their circularity was not 0.5 or more. Sample 19 had an exposed area ratio of the copper-tin alloy layer that exceeded the specified range. This is presumably due to the long cooling time required to lower the temperature of the plated substrate to 50°C in the reflow treatment process. Samples 28 to 30 had a larger average thickness of the tin layer than the others, resulting in a smaller exposed area ratio of the copper-tin alloy layer.

[0080] Figure 5 is a backscattered electron (BSE) image of the cross section of sample 3. It can be seen that a copper-tin alloy layer with a concave-convex shape is formed on the nickel layer, and a tin layer is formed on the nickel layer. It was also confirmed that the copper-tin alloy layer is composed of a Cu3Sn layer formed in a small amount and dispersed manner on the nickel layer, and a Cu6Sn5 layer formed to cover the Cu3Sn layer and the nickel layer where no Cu3Sn layer exists.

[0081] In comparison with these samples, sample 31 had a large Spc and a large amount of wear, although the average thickness of the tin layer was within the specified range. This is presumed to be due to the high temperature in the first furnace during the reflow treatment process. Samples 32 and 37 had a copper-tin alloy layer that was too thin to measure Spc and circularity, and also had a high friction coefficient and a large amount of wear. This is due to the fact that either the first or second heating treatment in the reflow treatment process was not performed. Samples 33 and 34 had a thin copper-tin alloy layer and a small Spc, so the friction coefficient was high and the wear amount was large. This is presumed to be due to an insufficient first heat treatment in the reflow treatment process. In sample 35, the temperatures in the first furnace and the second furnace during the reflow treatment were too high, leading to a large Spc and a large amount of wear. In addition, the tin layer was thin, leading to a high contact resistance. In sample 36, the first heat treatment time in the reflow treatment step was too long, so the tin layer became thin and the contact resistance was high.

[0082] Samples 38 and 39 had a high friction coefficient and a large amount of wear due to their small Spc. This is presumably due to the insufficient second heat treatment in the reflow treatment process. In sample 40, the temperature in the second furnace during the reflow treatment was too high, so Spc was large and the wear resistance was reduced. On the other hand, the tin layer was thin, so the contact resistance was high. In sample 41, the second heat treatment time in the reflow treatment step was too long, so the tin layer became thin and the contact resistance was high. In sample 42, the tin plating layer was too thick, resulting in a thick tin layer and a high coefficient of friction.

[0083] In Samples 43 and 44, the copper plating layer remained even after the reflow treatment process. In sample 43, the copper plating layer met the specified thickness, but the tin plating layer did not meet the specified thickness, so the exposure rate after the reflow treatment was greater than the specified value and Spc was smaller, resulting in a large amount of wear. In addition, the tin layer was thin, so the contact resistance was high. On the other hand, in sample 44, the thickness of the copper plating layer was thicker than the specified range, so the average thickness of the copper-tin alloy layer after the reflow treatment was thicker than the specified range and the tin layer was thinner, resulting in a larger exposure rate than the specified value. In addition, some of the copper plating layer was found to remain after the reflow treatment, and the shape of the copper-tin alloy layer became gentle, so Spc was slightly smaller and within the specified range. Therefore, the amount of wear was somewhat large. In addition, the tin layer was thin, so the contact resistance was high.

[0084] In sample 45, the thickness of the copper plating layer and the average thickness of the copper-tin alloy layer were thinner than the specified range, so that part of the copper-tin alloy was replaced with nickel, the shape of the copper-tin alloy became steep, and Spc was larger than the specified range, resulting in a high friction coefficient and a large amount of wear. For sample 46, the nickel layer was too thick, so cracks occurred during indentation, and the friction coefficient, wear amount, and contact resistance were not evaluated. Sample 47 had high contact resistance because the nickel layer was too thin.

[0085] Next, the above samples were arbitrarily combined, and the difference in Spc and circularity of the copper-tin alloy layer was obtained, and the friction coefficient was measured. In this case, one was used as a male terminal and the other was used as a female terminal, and the friction coefficient was measured in the same manner as above. The results are shown in Table 4.

[0086] [Table 4]

[0087] All combinations have a good friction coefficient, but the difference in Spc between the female terminal and the male terminal is 200 mm. -1 More than 1200mm -1 The following samples 53 to 62 show particularly good friction coefficients. The difference in circularity in all cases was 0.4 or less. It is assumed that the appropriate difference in the shape of the copper-tin alloy layer reduces the contact points of the copper-tin alloy layer during sliding, and the actual contact area is reduced, resulting in smaller sliding marks. Note that sample 52 is within the range of the present invention for both the male and female terminals, but the difference in Spc is 200 mm. -1 Because the friction coefficient was slightly higher than the The Spc of one side terminal of samples 55, 56, 59, and 60 is 2200 mm -1 However, since the Spc of the other terminal is appropriate, the friction coefficient is low. On the other hand, for sample 51, the Spc for both the female and male terminals was 2200 mm -1 The friction coefficient was high, exceeding the limit of 1200 mm. -1 Samples 63 and 64, which exceeded 100%, showed slightly higher friction coefficients. This is presumably because the uneven shape of the copper-tin alloy layer of one terminal is thinner than that of the other terminal, which may cause breakage during sliding. [Explanation of symbols]

[0088] 1. Connector terminal material 10 Terminal section 11,12 Connecting members 13 Connection 14 Shoulder section 15 Board fixing part 21 Base material 22 Membrane 23 Nickel layer 24 Copper-tin alloy layer 25 Tin layer 31 Nickel plating layer 32 Copper plating layer 33 Tin plating layer 35 Substrate with plating layer

Claims

1. A coating is formed on a surface of a substrate made of copper or a copper alloy, the coating having a nickel layer made of nickel or a nickel alloy formed on the surface of the substrate, a copper-tin alloy layer made of an alloy of copper and tin formed on the nickel layer, and a tin layer made of tin or a tin alloy formed on the copper-tin alloy layer, The average thickness of the nickel layer is 0.05 μm or more and 3.00 μm or less, The arithmetic mean curvature Spc of the peaks on the surface of the copper-tin alloy layer is 700 mm -1 More than 2200mm -1 the tin layer has an average thickness of 0.05 μm or more and 2.00 μm or less, and the copper-tin alloy layer has an average thickness of 0.15 μm or more and 1.55 μm or less.

2. A terminal material for a connector as described in claim 1, characterized in that the tin layer of the coating is removed to expose the copper-tin alloy layer, and the circularity of the copper-tin alloy particles on the surface of the exposed copper-tin alloy layer is 0.5 or more.

3. 3. A terminal material for a connector as described in claim 1 or 2, characterized in that a portion of the copper-tin alloy layer is exposed on the surface of the tin layer, and the exposed area ratio of the copper-tin alloy layer on the surface of the tin layer is 5% or more and 70% or less.

4. 3. The terminal material for a connector according to claim 1, further comprising a connection portion to be connected to a mating portion and a board fixing portion to be fixed to a board, and the coating is formed at least on the connection portion.

5. 5. The terminal material for a connector according to claim 4, wherein the board fixing portion has a tin surface layer made of tin or a tin alloy formed on the entire front, back and both side surfaces.

6. A connector has one terminal and another terminal that can be connected to each other, at least one of the one terminal and the other terminal is made of the terminal material for a connector according to claim 1 or 2, and a difference in arithmetic mean curvature Spc of peaks on the surface of the copper-tin alloy layer between the one terminal and the other terminal is 200 mm -1 More than 1200mm -1 A connector characterized by the following range:

7. 7. The connector according to claim 6, wherein a difference in circularity of the copper-tin alloy particles on the surface of the copper-tin alloy layer between the one terminal and the other terminal is in a range of 0.4 or less.

8. a plating layer forming step of laminating a nickel plating layer made of nickel or a nickel alloy, a copper plating layer made of copper or a copper alloy, and a tin plating layer made of tin or a tin alloy in this order on a surface of a base material made of copper or a copper alloy to form a base material with a plating layer; and a reflow treatment step of carrying out a reflow treatment of heating the base material with a plating layer, In the plating layer forming step, the nickel plating layer is formed to a thickness of 0.05 μm or more and 3.00 μm or less, the copper plating layer is formed to a thickness of 0.10 μm or more and 0.70 μm or less, and the tin plating layer is formed to a thickness of 0.20 μm or more and 2.90 μm or less, The reflow treatment step includes a first heating treatment in which the base material with the plating layer is passed through a first heating furnace set to a first furnace temperature of 150° C. or more and 270° C. or less in an air atmosphere for a time of 3 seconds or more and 30 seconds or less to heat the base material with the plating layer to a temperature lower than the melting point of tin, a second heating treatment in which the base material with the plating layer is passed through a second heating furnace set to a second furnace temperature of 232° C. or more and 350° C. or less, which is higher than the first furnace temperature, for a time of 3 seconds or more and 35 seconds or less to heat the base material with the plating layer, and a cooling treatment in which the base material with the plating layer is quenched immediately after the tin plating layer is melted by the second heating treatment, In the cooling treatment, the cooling time until the temperature of the base material with a plating layer reaches 50° C. is set to 4 seconds or more and 60 seconds or less. A method for producing a terminal material for a connector comprising the steps of:

Citation Information

Patent Citations

  • Conducting material for connection parts and manufacturing method therefor

    JP2007100220A

  • Metallic material for connector

    JP2011012320A

  • Terminal for substrate and connector for substrate using the same

    JP2012248281A

  • Tin-plated copper alloy terminal material excellent in insertion / removal properties and production method thereof

    JP2014240520A

  • Tin-plated copper alloy terminal material

    JP2015143385A